Organic synthesis in a modular robotic system driven by a chemical programming language - Steiner, Sebastian; Wolf, Jakob; Glatzel, Stefan; Andreou, Anna; Granda, Jarosław M; Keenan, Graham; Hinkley, Trevor; Aragon-Camarasa, Gerardo; Kitson, Philip J; Angelone, Davide; Cronin, Leroy (Science (American Association for the Advancement of Science), 2019)
The synthesis of complex organic compounds is largely a manual process that is often incompletely documented. To address these shortcomings, we developed an abstraction that maps commonly reported methodological instructions into discrete steps amenable to automation. These unit operations were implemented in a modular robotic platform by using a chemical programming language that formalizes and controls the assembly of the molecules. We validated the concept by directing the automated system to synthesize three pharmaceutical compounds, diphenhydramine hydrochloride, rufinamide, and sildenafil, without any human intervention. Yields and purities of products and intermediates were comparable to or better than those achieved manually. The syntheses are captured as digital code that can be published, versioned, and transferred flexibly between platforms with no modification, thereby greatly enhancing reproducibility and reliable access to complex molecules.